Cancer mortality in Europe in 2015 and an overview of trends since 1990. (30th May 2019) - Bertuccio, P; Alicandro, G; Malvezzi, M; Carioli, G; Boffetta, P; Levi, F; La Vecchia, C; Negri, E
Abstract: Background: Cancer mortality in Europe has been decreasing since the late 1980s or 1990s in some countries with different patterns in many areas. In this study, we updated trends in cancer mortality in Europe. Materials and methods: We extracted data from the World Health Organization mortality database for 24 cancer sites, 36 European countries and the European Union (EU) as a whole over the 1990–2017 period. We computed age-standardized death rates per 100 000 person-years, and we carried out a joinpoint regression analysis of mortality trends from all cancers and selected major neoplasms. The estimated annual percent change (APC) for each identified linear segment, and the weighted average APC (AAPC) over the entire study period were provided as summary measures of the changes in rates over the time period. Results: In 2015, the age-standardized mortality rates from all cancers in the EU were 137.5 deaths per 100 000 in men and 85.7 in women. Eastern European countries showed the highest rates with values over 150 deaths per 100 000 in men and over 100 deaths per 100 000 in women. Mortality from all cancers in the EU declined annually by 1.5% in men since 2006 and by 0.8% in women since 2007. Most cancer sites showed decreasing trends, with steady declines over the whole period for cancers of stomach, intestines, lung in men, breast and prostate. Unfavourable mortality trends persisted for cancers of liver, lung in women, pancreas, besides skin and kidney in men. Conclusions: The downward trends in total cancer mortality in Europe still continue over the last decade. However, the trends were less favourable in most eastern European countries. Tobacco control in men (but not in women), improvements in diagnosis and therapy were the main underlying factors of these trends.